Arthroscopic Versus Open Management of Diffuse-Type Tenosynovial Giant Cell Tumor of the Knee: A Meta-analysis of Retrospective Cohort Studies. (9th December 2021) - Chandra, Akhil A.; Agarwal, Shreya; Donahue, Ahna; Handorf, Elizabeth; Abraham, John A.
Abstract : Background: Whether arthroscopic or open surgical management for diffuse-type tenosynovial giant cell tumor (D-TGCT) of the knee is associated with a lower rate of recurrence is unknown. Methods: PubMed, Scopus, Web of Science, Cochrane, and EMBASE were searched on December 3, 2020. Retrospective studies that reported on recurrence rates for arthroscopic versus open management of D-TGCT were included. A total of 16 studies evaluating 1143 patients with D-TGCT of the knee were included (nopen = 551, narthroscopic = 350 patients, and narthroscopic/open = 23 patients). Random-effects meta-analyses were used to summarize and compare the reported recurrence rates, stratified by approach and overall recurrence. The meta-analysis was registered with PROSPERO. Results: The recurrence rate per year (incidence) for arthroscopic procedures was 0.11 (95% CI 0.08 to 0.16, P < 0.0001) and for open procedures was 0.07 (95% CI 0.04 to 0.13, P < 0.0001). There was a 1.56 times (95% CI 1.04 to 2.34, P = 0.0332) increased risk of recurrence when treating D-TGCT of the knee with an arthroscopic approach. When evaluating only the subset of studies that had data for both arthroscopic and open approaches, the incidence rate per year for arthroscopic procedures was 0.17 (95% CI 0.11 to 0.27, P < 0.0001) and for open procedures was 0.11 (95% CI 0.06 to 0.19, P < 0.0001). The rate of overall complications was 0.04 (95% CI 0.01 to 0.08, P < 0.0001). Conclusion: Arthroscopic surgical management of D-TGCT of the knee in our study resulted in a 1.56 times risk of recurrence as compared with the open approach. The percent of overall complications was minimal.